Risk Management in Gaining Profitability of Banking Companies - Saputera, Denny (Universitas Serang Raya, 2021)
Profitability is a bank's ability to earn a profit during a certain period. The amount of profitability of a company tends to be influenced by various kinds of risks. The risks that occur will cause losses to the bank if it is not detected and not managed properly. The purpose of this study is to determine the effect of credit risk, operational risk, and liquidity risk on the profitability of rural banks in the city for the 2019 period. The number of samples taken is 10 rural banks, through purposive sampling technique. The data collection method used is the non-participant observation method with multiple linear regression data analysis techniques. Based on the results of the analysis, it was found that credit risk had no significant positive effect on profitability. Operational risk has a significant negative effect on profitability. Liquidity risk has a significant positive effect on profitability